2020
DOI: 10.3390/antibiotics9080512
|View full text |Cite
|
Sign up to set email alerts
|

Content and Mechanism of Action of National Antimicrobial Stewardship Interventions on Management of Respiratory Tract Infections in Primary and Community Care

Abstract: A major modifiable factor contributing to antimicrobial resistance (AMR) is inappropriate use and overuse of antimicrobials, such as antibiotics. This study aimed to describe the content and mechanism of action of antimicrobial stewardship (AMS) interventions to improve appropriate antibiotic use for respiratory tract infections (RTI) in primary and community care. This study also aimed to describe who these interventions were aimed at and the specific behaviors targeted for change. Evidence-based guidelines, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…A recent study investigating behaviors related to antimicrobial stewardship for respiratory tract infections in primary care found that 5 of 32 were community pharmacy behaviors, mostly patient education [ 34 ]. A study by Revolinski et al showed varied antimicrobial stewardship practices in community pharmacies, with patient education and allergy assessment being among the most prevalent [ 35 ].…”
Section: Antimicrobial Stewardship In Community Pharmacymentioning
confidence: 99%
“…A recent study investigating behaviors related to antimicrobial stewardship for respiratory tract infections in primary care found that 5 of 32 were community pharmacy behaviors, mostly patient education [ 34 ]. A study by Revolinski et al showed varied antimicrobial stewardship practices in community pharmacies, with patient education and allergy assessment being among the most prevalent [ 35 ].…”
Section: Antimicrobial Stewardship In Community Pharmacymentioning
confidence: 99%
“…Second, we conducted a rapid review of intervention studies to identify research evidence on effective AMS interventions. We then compared these research interventions with previously identified national AMS interventions 6 to see which effective interventions have been already nationally implemented. Third, we conducted a behavioural analysis, using behaviour sciences frameworks and matrices, to compare the extent to which national and research AMS interventions (stage 2) address the key influences on antibiotic prescribing (stage 1).…”
Section: Methodsmentioning
confidence: 99%
“… 5 Recently, 39 nationally implemented interventions (with 22 targeted at prescribers) were identified that aimed at reducing antibiotic prescribing and use for RTIs in England alone. 6 Considering the large number of interventions and the typically modest effects, it would be informative to identify how well the interventions address influences on antibiotic prescribing and whether interventions have ‘gaps’ which could highlight areas for improvement.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations